Functional Vision Disorder - Egan, Robert A.; LaFrance, W. Curt, Jr. (Seminars in Neurology, 2015)
Functional vision disorder (FVD) is a common problem seen in many neurologic and ophthalmologic practitioners' offices and may occur in isolation or in the presence of medical illness. This disorder presents with visual or oculomotor symptoms and manifests as vision loss in one or both eyes, visual field loss, double vision, oscillopsia, anisocoria, blepharospasm, or ptosis. Manual perimetry is the most effective method for determining functional visual loss, and the presence of a central scotoma in a functional visual field signifies that a neuropathophysiologic process is almost certainly present. The exact neuropathophysiologic mechanism of this disorder is unknown; however, information can be drawn from the small studies of FVD samples and studies examining neuropsychiatric factors in other conversion disorder semiologies. Psychological and psychiatric interventions can be useful in treating these patients.
Keywords: functional vision disorder; functional visual loss; functional vision loss; nonorganic visual loss; psychogenic; conversion disorder